Literature Review: The Effect of Social Stigma on Children with Intellectual Disabilities - Assyahidah, Aida Hanifah; Shilfiyani, Shela Pramudya; Kusmiati, Yulia; Oktaviani, Mila; Yaziid, Belvanisa Fitrilya Rizky; Maulidina, Citra Ashri (Universitas Negeri Surabaya, 2025)
Children with intellectual disabilities often have to deal with negative views from the surrounding environment. Negative perceptions of disability in society are often exacerbated by a lack of education and understanding about disability. This research aims to provide a clear picture of the social stigma faced by children with intellectual disabilities and how it affects their lives. This research uses the Systematic Literature Review (SLR) method. The results of this study show that there are negative viewpoints regarding stigma and discrimination in the family, community, and academic institutions. Such as the labeling of “stupid child,” “bad child,” “cursed child,” or “family burden,” often shunned, treated badly/discriminated, lack of services, such as gaps in education, health services, and social services, and lack of support for maximum growth and development in children.